3D simulation of laminar flow and heat transfer in V-baffled square channel - Promvonge, Pongjet; Jedsadaratanachai, Withada; Kwankaomeng, Sutapat; Thianpong, Chinaruk (My University, 2012)
The article presents a numerical investigation on laminar flow and heat transfer characteristics in a three-dimensional isothermal wall square-channel fitted with inline 45̊ V-shaped baffles on two opposite walls. The computations based on the finite volume method with the SIMPLE algorithm have been conducted for the airflow in terms of Reynolds numbers ranging from 200 to 2000. The inline V-baffles with its V-tip pointing downstream and the attack angle (or half V-apex angle) of 45̊ relative to the flow direction are mounted repeatedly on the lower and upper walls. The baffled channel flow shows a fully developed periodic flow and heat transfer profile for BR=0.2 at x/D≊8 downstream of the inlet. Influences of different baffle height ratios (BR) and pitch ratios, (PR) on thermal behaviors for a fully developed periodic condition are investigated. It is apparent that the longitudinal counter-rotating vortex flows created by the V-baffle can induce impingement/attachment flows over the walls resulting in greater increase in heat transfer over the test channel. Apart from speeding up the fully developed periodic flow pattern, the rise of the BR leads to the increase in Nu/Nu 0 and f/f 0 values while that of the PR provides an opposite trend. The V-baffle performs better than the angled baffle at a similar condition. The V-baffle with BR=0.2 and PR=1.5 yields the maximum thermal performance of about 3.8 whereas the Nu/Nu 0 is some 14 times above the smooth channel at higher Re. © 2011 Elsevier Ltd.
Keywords: Heat transfer; Laminar flow; Periodic flow; Square channel; V-shaped baffle